TINDAKAN PENANGANAN KEGAWATDARURATAN PADA PASIEN DISPEPSIA DENGAN ASUHAN KEPERAWATAN DI RUMAH SAKIT TK III DR. REKSODIWIRYO PADANG - shanti dafris (Akper Kesdam I/Bukit Barisan Padang, 2022)
Dyspepsia is a medical condition characterized by pain or discomfort in the pit of the stomach. Based on data from TK III Hospital, dr. Reksodiwiryo Padang, Dyspepsia cases are increasing every month, in 2021 based on data for the last 3 months of dyspepsia cases in October with 42 cases, November with 77 cases and December with 82 cases. In January 2022, 89 cases of dyspepsia were recorded. This study aims to carry out nursing care for dyspeptic patients at TK III Hospital dr.Reksodiwiryo Padang. The research design used is a case study. The participant in this study is a single unit, namely Mr. A. This research was conducted from 7 November to 10 November 2022 in the Bagindo Aziz Chan room at the TK III Hospital Dr. Reksodiwiryo Padang. Data collection uses the format of assessment, interview, physical examination and documentation. The data analysis stage is done by collecting data, presenting data, and making conclusions. The results of this case study research at the assessment stage found that Mr. A was 19 years old. The patient was admitted with dyspepsia because he had heartburn with a pain scale of 7. Based on the data obtained in the field, there were three diagnoses that emerged during the assessment, namely acute pain b.d. agents of biological injury (stomach mucosal gastric) d.d. complaining of pain, grimacing, disturbed sleep patterns b.d. Physical Restraint d.d Complaining of difficulty sleeping, Risk of Hypovolemia d.d Lack of fluid intake. The intervention was resolved and the patient went home.